A uniform‐shear rate microfluidic bioreactor for real‐time study of proplatelet formation and rapidly‐released platelets. (13th October 2017) - Martinez, Andres F.; McMahon, Richard D.; Horner, Marc; Miller, William M.
Abstract : Platelet transfusions, with profound clinical importance in blood clotting and wound healing, are entirely derived from human volunteer donors. Hospitals rely on a steady supply of donations, but these methods are limited by a 5‐day shelf life, the potential risk of contamination, and differences in donor/recipient histocompatibility. These challenges invite the opportunity to generate platelets ex vivo. Although much progress has been made in generating large numbers of culture‐derived megakaryocytes (Mks, the precursor cells to platelets), stimulating a high percentage of Mks to undergo platelet release remains a major challenge. Recent studies have demonstrated the utility of shear forces to enhance platelet release from cultured Mks. In this study, we performed a computational fluid dynamics (CFD) analysis of several published platelet microbioreactor systems, and used the results to develop a new 7‐µm slit bioreactor—with well‐defined flow patterns and uniform shear profiles. This uniform‐shear‐rate bioreactor (USRB‐7µm) permits real‐time visualization of the proplatelet (proPLT) formation process and the rapid‐release of individual platelet‐like‐particles (PLPs), which has been observed in vivo, but not previously reported for platelet bioreactors. We showed that modulating shear forces and flow patterns had an immediate and significant impact on PLP generation. Surprisingly, using a single flow instead of dual flows led to an unexpected six‐fold increase in PLP production. By identifying particularly effective operating conditions within a physiologically relevant environment, this USRB‐7µm will be a useful tool for the study and analysis of proPLT/PLP formation that will further understanding of how to increase ex vivo platelet release. © 2017 American Institute of Chemical Engineers Biotechnol. Prog., 33:1614–1629, 2017